Communication in non-communicable diseases (NCDs) and role of immunomodulatory nutraceuticals in their management - Kumar, Abhiram; Sakhare, Kalyani; Bhattacharya, Dwaipayan; Chattopadhyay, Raktim; Parikh, Purvish; Narayan, Kumar P.; Mukherjee, Anubhab (Frontiers in Nutrition, 2022)
Conveyance of pathogens between organisms causes communicable diseases. On the other hand, a non-communicable disease (NCD) was always thought to have no causative transmissible infective agents. Today, this clear distinction is increasingly getting blurred and NCDs are found to be associated with some transmissible components. The human microbiota carries of a congregation of microbes, the majority and the most widely studied being bacteria in the gut. The adult human gut harbours ginormous inhabitant microbes and the microbiome accommodates 150-fold more genes than the host genome. Microbial communities share a mutually beneficial relationship with the host especially with respect to host physiology including digestion, immune responses, and metabolism. This review delineates the connection between environmental factors such as infections leading to gut dysbiosis and NCDs and explores the evidences regarding possible causal link between them. We also discuss the evidences regarding the value of appropriate therapeutic immunomodulatory nutritional interventions to reduce the development of such diseases. We behold such immunomodulatory effects have the potential to influence various NCDs and restore homeostasis. We believe that the beginning of the era of microbiota-oriented personalized treatment modalities is not far away.